Exploring Students' Perceptions of Demonstration Tools For Respiratory System Learning: A Qualitative Approach - Kua, Maria Yuliana; Gelu, Afrianus; Foa, Anna Julita; Dedo, Bernardus Ardy; Itu, Kristina Evanjelina (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Science learning in the industrial revolution era also encourages teachers to provide learning media that support students' characters. One of the supporting media is the use of teaching aids. Limited resources pose a significant challenge for students. Students at State Junior High School 1 Golewa are also experiencing this issue. This study aims to identify students' perceptions of the use of human respiratory system teaching aids. Methodology: We conducted the study on Grade VIII students of State Junior High School 1 Golewa using observation and questionnaire methods. Data collection techniques involved participatory observation and student response questionnaires. The data were analyzed descriptively. Main Findings: The results showed that the use of teaching aids increased students' involvement and understanding of the concept of the respiratory system. Most students stated that teaching aids helped them understand the material better, increased their interest in learning, and encouraged activity and interaction during learning. Novelty/Originality of this study: This results confirm that teaching aids play an important role in improving the quality of science learning. The conclusion of this study is that the use of teaching aids is effective in increasing students' understanding of the human respiratory system material.